Histopathological, Histomorphometrical, and Radiographical Evaluation of Injectable Glass-Ceramic-Chitosan Nanocomposite in Bone Reconstruction of Rat. (8th February 2015) - Seyedmajidi, Maryam; Rabiee, Seyedmahmood; Haghanifar, Sina; Seyedmajidi, Seyedkamal; Jorsaraei, Seyed Gholam ali; Alaghehmand, Homayoun; Jamaatlu, Naghmeh; Bijani, Ali
Abstract : Background . Bone defects following tumor resection and osteolysis due to bone lesions, periodontal tissue disorders, and bone reconstruction are challenges that surgeons face. Gass-ceramic-chitosan nanocomposite contains chitosan, a derivative of crustaceans' exoskeleton. Methods . Thirty-two 6–8-week-old male Wistar rats were chosen. One hole on each right and left tibia was made. The right tibia holes were filled with injectable glass-ceramic-chitosan nanocomposite, and the left tibia holes were left empty. After 7, 14, 28, and 60 days, histopathological, histomorphometrical, and radiographical assessments were performed. Results . Radiographic density on days 7 and 14 was significantly higher in the right tibias than in the left tibias. Trabecular bone thickness, which was higher in the right tibias, increased from day 7 to day 60 in both right and left tibias, although not significantly. Conclusions . Glass-ceramic-chitosan nanocomposite is suggested for use in bone repair in cases of bone loss. More histopathological, histomorphometrical, and radiographical assessments are also recommended.